2002
DOI: 10.1002/em.10073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of mutations at the HPRT and TK loci of human lymphoblastoid cells after combined treatments with 3′‐azido‐3′‐deoxythymidine and 2′,3′‐dideoxyinosine†

Abstract: Combinations of antiretroviral drugs that include nucleoside reverse transcriptase inhibitors (NRTIs) are superior to single-agent regimens in treating or preventing HIV infection, but the potential long-term health hazards of these treatments in humans are uncertain. In earlier studies, our group found that coexposure of TK6 human lymphoblastoid cells to 3'-azido-2',3'-dideoxythymidine (AZT) and 2',3'-dideoxyinosine (ddI), the first two NRTIs approved by the FDA as antiretroviral drugs, produced multiplicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Therefore, we cannot conclude with certainty that the elevated reticulocyte micronucleus frequencies observed in ZDV-exposed infants in our study will be associated with a higher risk of future disease in these infants compared with healthy, non-exposed individuals. However, we are concerned about the long-term health implications for these infants because the MN increases noted in this study add to the growing body of evidence that ZDV readily induces genetic damage (mutational and clastogenic) in both nuclear and mitochondrial DNA in a variety of in vitro and in vivo test systems (Sussman et al, 1999;Poirier et al, 2004;Chan et al, in press;Von Tunglen et al, 2004;Meng et al, 2002;Olivero et al, 2002;Bishop et al, 2004;Witt et al, 2004;Meng et al, 2000;Hong et al, in press;Olivero, in press). …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, we cannot conclude with certainty that the elevated reticulocyte micronucleus frequencies observed in ZDV-exposed infants in our study will be associated with a higher risk of future disease in these infants compared with healthy, non-exposed individuals. However, we are concerned about the long-term health implications for these infants because the MN increases noted in this study add to the growing body of evidence that ZDV readily induces genetic damage (mutational and clastogenic) in both nuclear and mitochondrial DNA in a variety of in vitro and in vivo test systems (Sussman et al, 1999;Poirier et al, 2004;Chan et al, in press;Von Tunglen et al, 2004;Meng et al, 2002;Olivero et al, 2002;Bishop et al, 2004;Witt et al, 2004;Meng et al, 2000;Hong et al, in press;Olivero, in press). …”
Section: Discussionmentioning
confidence: 89%
“…First, DNA incorporation of ZDV and resulting genetic effects may be enhanced by the presence of additional nucleoside analogues such as lamivudine or didanosine (Meng et al, 2002;Bishop et al, 2004;Witt et al, 2004;Meng et al, 2000), although neither of these two nucleosides alone induces micronuclei in mice (Phillips et al, 1991;Von Tungeln et al, 2004;Witt et al, 2004;Von Tungeln et al, 2002;Von Tungeln et al, in press). All women in this study who received ZDV during the prenatal period also received lamivudine, whereas infants received ZDV alone during postpartum treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AZT also causes point mutations in human cells exposed in culture and in skin and lung neoplasms from in utero exposed mice [Zhang et al, 1998;Meng et al, 2002, Hong et al, 2007. The finding of increased GPA N/N Vfs in AZT-3TC exposed mother-child pairs is noteworthy because it reflects genetic events leading to LOH, a key mechanism directly relevant to NRTI-induced mutagenesis as shown by LOH in the thymidine kinase (TK) and adenine phosphoribosyltransferase (APRT) reporter genes in human lymphoblastoid cells exposed in vitro to AZT, or AZTdidanosine, and at the Tk locus of mice exposed in utero to AZT [Meng et al, 2000a[Meng et al, ,b,c, 2002Mittelstaedt et al, 2004;Von Tungeln et al, 2004.…”
Section: Discussionmentioning
confidence: 99%
“…ddI also appears to potentiate the mutagenicity of AZT because when human TK6 lymphoblastoid cells were incubated with AZT, ddI or a mixture of AZT and ddI, the combination of AZT and ddI increased the incorporation of AZT into cellular DNA and the mutant frequency within the hypoxanthine-guanine phosphoribosyltransferase (HPRT) and thymidine kinase (TK) genes (Meng et al, 2000). The increase in mutant frequency was attributed to an increase in point mutations (Meng et al, 2002).In previous work we demonstrated that AZT, but not the nucleoside analog lamivudine [(±)2¢,3¢-dideoxy-3¢-thiacytidine, 3TC], was genotoxic to neonatal mice, as indicated by an increased mutant frequency in the Tk gene and an increased frequency of micronucleated polychromatic erythrocytes (PCEs). Furthermore, 3TC in combination with AZT did not alter the responses observed with AZT alone (Von Tungeln et al, 2002).…”
mentioning
confidence: 99%